Preparation and X‐ray analysis of potassium (2, 3‐dichlorophenyl)glucosinolate. Issue 6 (16th May 2014) - Vo, Quan V.; Trenerry, Craige; Rochfort, Simone; White, Jonathan; Hughes, Andrew B.
<x xml:space="preserve">Abstract</x> There has been much interest in obtaining crystals for crystallographic analysis of biologically active glucosinolates. Crystals of potassium (2, 3‐dichlorophenyl)glucosinolate were obtained as a dual solvate, containing one methanol and one ethanol molecule of crystallization, K+·C13H14Cl2NO9S2−·CH3OH·C2H5OH. The three‐dimensional polymeric network consists of chains containing the potassium ions coordinated and bridged by sugar O atoms, which run parallel to the a axis and are further crosslinked through the sugar molecules. The channels of this network are occupied by the dichlorophenyl substituents and the ethanol and methanol solvent molecules. The structure of the S‐(2, 3, 4, 6‐tetra‐O‐acetyl‐β‐D‐glucopyranosyl)‐2, 3‐dichlorophenylacetothiohydroxymate, C21H23Cl2NO10S, precursor has also been determined and the β‐configuration and Z isomer of the thiohydroximate substituent is confirmed.